Characteristics and distribution of the Opuntia (Cactaceae) representatives naturalized in Crimea - N. A. Bagrikova; Ya. A. Perminova (Труды по прикладной ботанике, генетике и селекции)
Background. Representatives of the Opuntia Mill. genus (Cactaceae), growing in natural habitats in South and North Americas, Mexico, Western India, and the Galapagos Islands, are widely used as ornamental, food and medicinal plants in different regions of the world. Many species have naturalized, and at least 27 species (or 14%) are invasive plants, thus posing a threat to local species and plant diversity. The largest numbers of naturalized species were observed in Spain, South Africa, and Australia. Studying the distribution of Opuntia Mill. representatives over Crimea is relevant because eight naturalized representatives of the genus have already been found in the region.Materials and methods. The information about Opuntia engelmannii Salm-Dyck var. lindheimeri (Engelm.) U. Guzman & Mandujano, O. fragilis (Nutt.) Haw., O. humifusa (Raf.) Raf., O. macrorhiza Engelm., O. phaeacantha Engelm. f. rubra Späth., O. polyacantha Haw., O. tortispina Engelm. & J.M. Bigelow, and O. tunoidea Gibbes is based on the research carried out in 2007–2021. Vegetation classification units were identified on the basis of geobotanical studies.Results. General characteristics and distribution of eight Opuntia representatives in natural and cultigenic areas are presented. It has been established that prickly pears were originally planted intentionally in Crimea, but later they spread in anthropogenically disturbed and seminatural biotopes, assigned to nine classes of vegetation (Quercetea pubescentis, Festuco-Brometea, Sedo-Scleranthetea, Koelerio-Corynephoretea, Artemisietea vulgaris, Asplenietea trichomanis, Cisto-Micromerietea julianae, Thero-Brachypodietea, and Pegano harmalae-Salsoletea vermiculatae). Opuntia humifusa and O. engelmannii var. lindheimeri have the widest distribution in Crimea. All species reproduce by seeds and vegetatively. The text is illustrated with photographs of the species and schematic maps of their distribution over the Crimean Peninsula.